PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RPP MELALUI KEGIATAN IHT (IN HOUSE TRAINING) - Hasyuni Harti (Ensiklopedia Education Review, 2022)
This study aims to: 1) To find out the steps for implementing IHT activities in preparing RPP to improve teacher professional competence for teachers at SMPN 15 Padang in carrying out learning. 2) To find out the improvement of teacher competence at SMPN 15 Padang in Developing Learning Implementation Plans through IHT activities. The subjects of this study were all teachers of SMPN 15 Padang. This research is School Action Research (PTS) which consists of two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. The data analysis technique used is comparative descriptive. From the results of the study it can be concluded that: 1) The steps for implementing IHT in order to improve the professional competence of teachers in preparing lesson plans at SMPN 15 Padang are as follows: (a) Delivering announcements to teachers about the implementation of IHT activities regarding the preparation of lesson plans; (b) Prepare guidance materials in the form of implementation of learning accompanied by simulations; (c) Preparing IHT instruments; (d) Carry out IHT activities without interfering with learning activities; and e) Carrying out observations in the classroom when learning activities are carried out by the teacher; and 2) IHT can improve the professional competence of SMPN 15 Padang teachers in preparing lesson plans. This is indicated by the increasing professional competence of teachers both in the preparation and implementation stages. This is indicated by the increase in competency achievement from 69.58 in the initial condition, to 72.81 at the end of Cycle 1 action, and increased to 83.13 in Cycle II action.Keywords: Competence, Teacher, RPP, In House Training.